Constrained Optimization and Optimal Control for Partial Differential Equations - Leugering, Günter; Engell, Sebastian; Griewank, Andreas; Hinze, Michael; Rannacher, Rolf; Schulz, Volker; Ulbrich, Michael; Ulbrich, Stefan (International series of numerical mathematics, 2012)
Introduction -- Constrained Optimization, Identification and Control -- Shape and Topology Optimization -- Model Reduction -- Discretization: Concepts and Analysis -- Applications.
Keywords: Partielle Differentialgleichung; Optimale Kontrolle